A bottle blank structure convenient for demoulding and preparation method thereof

By using an inner and outer polyester layer structure in the bottle preform, combined with materials such as PET resin, PEN resin and PET-PEN copolyester, the problem of difficult to achieve both mold release and dimensional stability of the bottle preform is solved, and efficient mold release and dimensional stability are achieved.

CN119388838BActive Publication Date: 2025-04-11FOSHAN HUAXIN HENGFENG POLYESTERIFCATION PACKAGING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411502693.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-04-11
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

In the prior art, it is difficult to have both the release property and the dimensional stability of the bottle preform, and the release property may easily become worse after the heat resistance is improved.

Method used

The bottle preform structure of the inner polyester layer and the outer polyester layer are arranged in sequence from the inside out. The inner polyester layer and the outer polyester layer both contain PET resin, PEN resin, PET-PEN copolyester, silane coupling agent modified nanosilica, antioxidant and mold release agent. By adjusting the ratio of raw materials, the heat resistance and dimensional stability are improved, and the mold release effect is improved.

Benefits of technology

Good mold release and dimensional stability of the bottle preform is achieved, and the problem of conflict between mold release and dimensional stability is avoided, while the transparency and interlayer bonding stability of the bottle preform are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119388838B_ABST
    Figure CN119388838B_ABST
Patent Text Reader

Abstract

The present application discloses a bottle blank structure that is easy to demould and a preparation method thereof, and relates to the field of bottle blank processing. The bottle blank structure that is easy to demould comprises an inner polyester layer and an outer polyester layer, wherein both the inner polyester layer and the outer polyester layer comprise PET resin, PEN resin, PET-PEN copolyester, silane coupling agent modified nano-silica, an antioxidant and a demoulding agent; in the inner polyester layer, the weight ratio of PET resin, PEN resin, PET-PEN copolyester, silane coupling agent modified nano-silica, an antioxidant and a demoulding agent is 100: (25-30): (10-15): (3-5): (1-2): (2-3); in the outer polyester layer, the weight ratio of PET resin, PEN resin, PET-PEN copolyester, silane coupling agent modified nano-silica, an antioxidant and a demoulding agent is 100: (10-15) (8-12): (3-5): (1-2): (4-6). The bottle blank of the present application has the advantages of good demoulding property and dimensional stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of bottle blank processing, and in particular to a bottle blank structure that is easy to demould and a preparation method thereof. Background Art

[0002] In the production process of plastic products, the bottle blank is a semi-finished product before molding, and its demoulding and dimensional stability have a decisive influence on the quality and production efficiency of the final product.

[0003] In order to improve the dimensional stability of the preform, it is usually necessary to improve the heat resistance of the preform. However, the improvement of the heat resistance of the preform is often accompanied by an increase in the melt viscosity, which easily leads to poor demoulding properties of the preform. Therefore, how to obtain a preform with good demoulding properties and good dimensional stability is currently a hot issue. Summary of the invention

[0004] In order to improve the problem in the related art that it is difficult to achieve both demoulding properties and dimensional stability of a preform, the present application provides a preform structure that is easy to demould and a preparation method thereof, which can obtain a preform with good demoulding properties and good dimensional stability.

[0005] In the first aspect, the present application provides a preform structure that is easy to demould, which adopts the following technical solution:

[0006] A bottle blank structure that is easy to demould comprises an inner polyester layer and an outer polyester layer which are sequentially arranged from the inside to the outside, wherein the inner polyester layer and the outer polyester layer both comprise PET resin, PEN resin, PET-PEN copolyester, silane coupling agent modified nano-silicon dioxide, an antioxidant and a demoulding agent; in the inner polyester layer, the weight ratio of the PET resin, PEN resin, PET-PEN copolyester, silane coupling agent modified nano-silicon dioxide, an antioxidant and a demoulding agent is 100:(25-30):(10-15):(3-5):(1-2):(2-3); in the outer polyester layer, the weight ratio of the PET resin, PEN resin, PET-PEN copolyester, silane coupling agent modified nano-silicon dioxide, an antioxidant and a demoulding agent is 100:(10-15)(8-12):(3-5):(1-2):(4-6).

[0007] In the present application, the bottle blank includes a two-layer structure of an inner polyester layer and an outer polyester layer, and the raw material composition of the inner polyester layer and the outer polyester layer is basically the same, but the raw material ratio is different. Wherein, both the inner polyester layer and the outer polyester layer are mixed with PEN resin and PET-PEN copolyester, and the addition of PEN resin can improve the heat resistance of the inner polyester layer and the outer polyester layer, while PET-PEN copolyester can improve the compatibility of PET resin and PEN resin, which is conducive to obtaining a bottle blank of a stable size. In addition, in the outer polyester layer, the amount of PEN resin and PET-PEN copolyester used is relatively more than that of the inner polyester layer, but the amount of release agent used is relatively more than that of the outer polyester layer, which can make the shrinkage rate of the outer polyester layer in the molding thickness direction slightly greater than that of the inner polyester layer, and at the same time, it will not cause the interlayer separation problem caused by the large difference in shrinkage rate between the inner polyester layer and the outer polyester layer in the molding thickness direction, which is convenient for demoulding of the bottle blank, and the dimensional stability of the bottle blank is good.

[0008] In some specific embodiments, the melt index of the PET resin is 0.8-1.2 g / 10 min (270° C. / 2.16 kg).

[0009] In the present application, the melt index of the PET resin is preferably in the range of 0.8-1.2 g / 10 min, so that a preform having good dimensional stability and being easy to blow mold can be obtained.

[0010] In some specific embodiments, the PEN resin has a melt index of 10-15 g / 10 min (275° C. / 2.16 kg).

[0011] In the present application, the melt index of the PEN resin is preferably 10-15 g / 10 min, which can improve the dimensional stability of the preform and obtain a preform that is easy to blow mold.

[0012] In some specific embodiments, the PET-PEN copolyester is a polycondensation product of terephthalic acid, 2,6-naphthalene dicarboxylic acid and ethylene glycol, wherein the molar ratio of terephthalic acid, 2,6-naphthalene dicarboxylic acid and ethylene glycol is (1.6-1.8): (0.2-0.4): (2.3-2.5).

[0013] In the present application, PET-PEN copolyester is a polycondensation product of terephthalic acid, 2,6-naphthalene dicarboxylic acid and ethylene glycol in a molar ratio of (1.6-1.8): (0.2-0.4): (2.3-2.5), which can improve the compatibility of PET resin and PEN resin and improve the transparency of the bottle blank.

[0014] In some specific embodiments, the preparation method of the PET-PEN copolyester comprises the following steps:

[0015] After mixing terephthalic acid, 2,6-naphthalene dicarboxylic acid and ethylene glycol, an esterification reaction is carried out at 220-240°C to obtain an esterification product; a polycondensation catalyst is added to the esterification product, the vacuum degree of the reaction system is controlled to be 0.1-1mbar, the temperature is controlled to be 260-290°C, and the reaction is carried out for 3-4h to obtain PET-PEN copolyester.

[0016] In the present application, the above method is used to prepare PET-PEN copolyester, which is beneficial to improve the product stability of PET-PEN copolyester, thereby improving the quality stability of the bottle blank.

[0017] In some specific embodiments, the polycondensation catalyst is a titanate catalyst.

[0018] In some specific embodiments, the antioxidant is a combination of antioxidant 1010 and antioxidant 168, and the weight ratio of the antioxidant 1010 to the antioxidant 168 is (1-1.5):1.

[0019] In the present application, the antioxidant adopts a composition of antioxidant 1010 and antioxidant 168 in a weight ratio of (1-1.5):1, which is beneficial to prevent thermal degradation of the polymer during processing and to improve the dimensional stability of the bottle blank.

[0020] In some specific embodiments, the release agent is silicone masterbatch.

[0021] In the present application, the mold release agent adopts silicone masterbatch, which can not only improve the processing performance of the raw material melting process, but also help to improve the demoulding effect of the bottle blank.

[0022] In some specific embodiments, the silane coupling agent modified nano-silica in the inner polyester layer is aminosilane coupling agent modified nano-silica, and the silane coupling agent modified nano-silica in the outer polyester layer is isocyanate silane coupling agent modified nano-silica.

[0023] In the present application, the silane coupling agent modified nano-silica in the inner polyester layer adopts aminosilane coupling agent modified nano-silica, and the silane coupling agent modified nano-silica in the outer polyester layer adopts isocyanate silane coupling agent modified nano-silica, which is beneficial to further improve the interlayer bonding stability of the bottle blank.

[0024] In a second aspect, the present application provides a method for preparing a bottle blank structure that is easy to demold, which adopts the following technical solution: A method for preparing a bottle blank structure that is easy to demold, comprising the following steps:

[0025] The raw materials of the inner polyester layer and the outer polyester layer are respectively added into two material barrels of a double-material injection molding machine, and heated and melted at 300-320° C. to obtain a plastic melt of the inner polyester layer and a plastic melt of the outer polyester layer;

[0026] The inner polyester layer plastic melt and the outer polyester layer plastic melt are processed into a double-layer bottle blank through an injection molding composite process. The double-layer bottle blank includes an inner polyester layer and an outer polyester layer arranged in sequence from the inside to the outside. After cooling, demolding is performed to obtain a bottle blank structure that is easy to demold.

[0027] In the present application, the above method is used to prepare a bottle blank, so that a double-layer bottle blank can be prepared, and at the same time, it is beneficial to improve the interlayer bonding stability of the double-layer bottle blank.

[0028] In summary, this application at least includes the following technical effects:

[0029] (1) In the present application, the bottle blank includes a two-layer structure of an inner polyester layer and an outer polyester layer. The raw material composition of the inner polyester layer and the outer polyester layer is basically the same, but the raw material ratio is different. Among them, both the inner polyester layer and the outer polyester layer are mixed with PEN resin and PET-PEN copolyester. The addition of PEN resin can improve the heat resistance of the inner polyester layer and the outer polyester layer, and PET-PEN copolyester can improve the compatibility of PET resin and PEN resin, which is conducive to obtaining a bottle blank with stable size. In addition, in the outer polyester layer, the amount of PEN resin and PET-PEN copolyester used is relatively more than that of the inner polyester layer, but the amount of release agent used is relatively more than that of the outer polyester layer, which can make the shrinkage rate of the outer polyester layer in the molding thickness direction slightly greater than that of the inner polyester layer. At the same time, it will not cause the problem of interlayer separation caused by the large difference in shrinkage rate between the inner polyester layer and the outer polyester layer in the molding thickness direction, which is convenient for demolding the bottle blank and has good dimensional stability.

[0030] (2) In the present application, the PET-PEN copolyester is a polycondensation product of terephthalic acid, 2,6-naphthalene dicarboxylic acid and ethylene glycol in a molar ratio of (1.6-1.8): (0.2-0.4): (2.3-2.5), which can improve the compatibility of PET resin and PEN resin and improve the transparency of the bottle blank.

[0031] (3) In the present application, the silane coupling agent modified nano-silica in the inner polyester layer adopts aminosilane coupling agent modified nano-silica, and the silane coupling agent modified nano-silica in the outer polyester layer adopts isocyanate silane coupling agent modified nano-silica, which is beneficial to further improve the interlayer bonding stability of the bottle blank. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a structural schematic diagram of a bottle blank structure that is easy to demould according to an embodiment of the present application.

[0033] Description of reference numerals:

[0034] 1. Inner polyester layer; 2. Outer polyester layer. DETAILED DESCRIPTION

[0035] The present application is further described below in conjunction with specific drawings and experiments.

[0036] Preparation Example

[0037] [Preparation Example 1]

[0038] A PET-PEN copolyester is a polycondensation product of an esterification product of terephthalic acid, 2,6-naphthalene dicarboxylic acid and ethylene glycol under the catalysis of a titanate catalyst, wherein the molar ratio of terephthalic acid, 2,6-naphthalene dicarboxylic acid and ethylene glycol is 0.7:1.3:2.4, and the titanate catalyst is tetrabutyl titanate.

[0039] The preparation method of PET-PEN copolyester comprises the following steps:

[0040] After mixing 0.7 kmol of terephthalic acid, 1.3 kmol of 2,6-naphthalenedicarboxylic acid and 2.4 kmol of ethylene glycol, an esterification reaction was carried out at 230° C. to obtain an esterification product;

[0041] 0.5 kg of tetrabutyl titanate was added to the esterification product, the vacuum degree of the reaction system was controlled to be 0.5 mbar, the temperature was controlled to be 275° C., and the reaction was carried out for 3.5 hours to obtain PET-PEN copolyester.

[0042] [Preparation Example 2]

[0043] A PET-PEN copolyester is a polycondensation product of an esterification product of terephthalic acid, 2,6-naphthalene dicarboxylic acid and ethylene glycol under the catalysis of a titanate catalyst, wherein the molar ratio of terephthalic acid, 2,6-naphthalene dicarboxylic acid and ethylene glycol is 1.7:0.3:2.4, and the titanate catalyst is tetrabutyl titanate.

[0044] The preparation method of PET-PEN copolyester comprises the following steps:

[0045] 1.7 kmol of terephthalic acid, 0.3 kmol of 2,6-naphthalenedicarboxylic acid and 2.4 kmol of ethylene glycol were mixed and subjected to esterification reaction at 230° C. to obtain an esterified product;

[0046] 0.5 kg of tetrabutyl titanate was added to the esterification product, the vacuum degree of the reaction system was controlled to be 0.5 mbar, the temperature was controlled to be 275° C., and the reaction was carried out for 3.5 hours to obtain PET-PEN copolyester.

[0047] [Preparation Example 3]

[0048] A PET-PEN copolyester is a polycondensation product of an esterification product of terephthalic acid, 2,6-naphthalene dicarboxylic acid and ethylene glycol under the catalysis of a titanate catalyst, wherein the molar ratio of terephthalic acid, 2,6-naphthalene dicarboxylic acid and ethylene glycol is 1:1:2.4, and the titanate catalyst is tetrabutyl titanate.

[0049] The preparation method of PET-PEN copolyester comprises the following steps:

[0050] After mixing 1 kmol of terephthalic acid, 1 kmol of 2,6-naphthalenedicarboxylic acid and 2.4 kmol of ethylene glycol, an esterification reaction was carried out at 230° C. to obtain an esterification product;

[0051] 0.5 kg of tetrabutyl titanate was added to the esterification product, the vacuum degree of the reaction system was controlled to be 0.5 mbar, the temperature was controlled to be 275° C., and the reaction was carried out for 3.5 hours to obtain PET-PEN copolyester.

[0052] Example

[0053] [Example 1]

[0054] A preform structure that is easy to demould, referring to Figure 1 , comprising an inner polyester layer 1 and an outer polyester layer 2 arranged in sequence from the inside to the outside.

[0055] The raw materials of the inner polyester layer 1 include 100kg PET resin (SK BR8040 from South Korea, with a melt index of 1g / 10min), 25kg PEN resin (Kolon Plaster KE901, with a melt index of 12g / 10min), 10kg PET-PEN copolyester (Preparation Example 1), 3kg aminosilane coupling agent KH550 modified nano-silica (obtained by immersing nano-silica in an aminosilane coupling agent KH550-ethanol solution with a mass concentration of 1%), 0.5kg antioxidant 1010, 0.5kg antioxidant 168 and 2kg silicone masterbatch.

[0056] The raw materials of the outer polyester layer 2 include 100kg PET resin (SK BR8040 from South Korea, with a melt index of 1g / 10min), 10kg PEN resin (Kolon Plaster KE901, with a melt index of 12g / 10min), 8kg PET-PEN copolyester (Preparation Example 1), 3kg aminosilane coupling agent KH550 modified nano-silica (obtained by immersing nano-silica in an aminosilane coupling agent KH550-ethanol solution with a mass concentration of 1%), 0.5kg antioxidant 1010, 0.5kg antioxidant 168 and 4kg silicone masterbatch.

[0057] In this embodiment, the method for preparing a preform structure that is easy to demould comprises the following steps:

[0058] The raw materials of the inner polyester layer 1 and the outer polyester layer 2 are respectively added into two barrels of a double-material injection molding machine, and heated and melted at 300° C. to obtain an inner polyester layer plastic melt and an outer polyester layer plastic melt;

[0059] The inner polyester layer plastic melt and the outer polyester layer plastic melt are processed into a double-layer bottle blank through an injection molding composite process. The double-layer bottle blank includes an inner polyester layer 1 and an outer polyester layer 2 arranged in sequence from the inside to the outside. After cooling, demolding is performed to obtain a bottle blank structure that is easy to demold.

[0060] [Example 2]

[0061] A preform structure that is easy to demould, referring to Figure 1 , comprising an inner polyester layer 1 and an outer polyester layer 2 arranged in sequence from the inside to the outside.

[0062] The raw materials of the inner polyester layer 1 include 100kg PET resin (SK BR8040 from South Korea, with a melt index of 1g / 10min), 30kg PEN resin (Kolon Plaster KE901, with a melt index of 12g / 10min), 15kg PET-PEN copolyester (Preparation Example 1), 5kg aminosilane coupling agent KH550 modified nano-silica (obtained by immersing nano-silica in an aminosilane coupling agent KH550-ethanol solution with a mass concentration of 1%), 1.2kg antioxidant 1010, 0.8kg antioxidant 168 and 3kg silicone masterbatch.

[0063] The raw materials of the outer polyester layer 2 include 100kg PET resin (SK BR8040 from South Korea, with a melt index of 1g / 10min), 15kg PEN resin (Kolon Plaster KE901, with a melt index of 12g / 10min), 12kg PET-PEN copolyester (Preparation Example 1), 5kg aminosilane coupling agent KH550 modified nano-silica (obtained by immersing nano-silica in an aminosilane coupling agent KH550-ethanol solution with a mass concentration of 1%), 1.2kg antioxidant 1010, 0.8kg antioxidant 168 and 6kg silicone masterbatch.

[0064] In this embodiment, the method for preparing a preform structure that is easy to demould comprises the following steps:

[0065] The raw materials of the inner polyester layer 1 and the outer polyester layer 2 are respectively added into two barrels of a double-material injection molding machine, and heated and melted at 300° C. to obtain an inner polyester layer plastic melt and an outer polyester layer plastic melt;

[0066] The inner polyester layer plastic melt and the outer polyester layer plastic melt are processed into a double-layer bottle blank through an injection molding composite process. The double-layer bottle blank includes an inner polyester layer 1 and an outer polyester layer 2 arranged in sequence from the inside to the outside. After cooling, demolding is performed to obtain a bottle blank structure that is easy to demold.

[0067] [Example 3]

[0068] A preform structure that is easy to demold, which differs from [Example 1] in that the PET-PEN copolyesters used in the inner polyester layer 1 and the outer polyester layer 2 are different. In this embodiment, the PET-PEN copolyester used in the inner polyester layer and the outer polyester layer is the PET-PEN copolyester prepared in [Preparation Example 2].

[0069] [Example 4]

[0070] A preform structure that is easy to demold, which differs from [Example 1] in that the PET-PEN copolyesters used in the inner polyester layer 1 and the outer polyester layer 2 are different. In this embodiment, the PET-PEN copolyester used in the inner polyester layer and the outer polyester layer is the PET-PEN copolyester prepared in [Preparation Example 3].

[0071] [Example 5]

[0072] A preform structure that is easy to demold, which differs from [Example 3] in that: the aminosilane coupling agent KH550 modified nano-silica in the inner polyester layer 1 and the outer polyester layer 2 is replaced by an equal amount of isocyanatepropyltriethoxysilane modified nano-silica (obtained by immersing and modifying the nano-silica in an isocyanatepropyltriethoxysilane-ethanol solution with a mass concentration of 1%).

[0073] [Example 6]

[0074] A preform structure that is easy to demold, which differs from [Example 3] in that: the aminosilane coupling agent KH550 modified nano-silica in the outer polyester layer 2 is replaced by an equal amount of isocyanatepropyltriethoxysilane modified nano-silica (obtained by immersing and modifying the nano-silica in an isocyanatepropyltriethoxysilane-ethanol solution with a mass concentration of 1%).

[0075] Comparative Example

[0076] [Comparative Example 1]

[0077] A bottle blank structure, which differs from [Example 1] in that the outer polyester layer 2 is replaced by the inner polyester layer 1.

[0078] [Comparative Example 2]

[0079] A bottle blank structure, which differs from [Example 1] in that: the inner polyester layer 1 is replaced by the outer polyester layer 2.

[0080] [Comparative Example 3]

[0081] A preform structure, which is different from [Example 1] in that PEN resin and PET-PEN copolyester are not added to the inner polyester layer 1 and the outer polyester layer 2.

[0082] Performance testing

[0083] 1. Mold release: 100 samples were randomly selected from the preforms prepared in each embodiment and comparative example to observe whether the surface of the preforms was damaged or deformed, and the number of preforms with damage or deformation was recorded.

[0084] 2. Dimensional stability: 20 samples without surface damage or deformation were randomly selected from the preforms prepared in each embodiment and comparative example, and the radial and height dimensions of the preforms were tested respectively. The standard deviation of the radial dimensions and the height dimensions of the 20 preforms were calculated. The smaller the standard deviation, the better the dimensional stability of the preform.

[0085] 3. Light transmittance: The light transmittance of the preforms prepared in the examples and comparative examples was tested with reference to GB / T 2410-2008 “Determination of light transmittance and haze of transparent plastics”.

[0086] 4. Structural stability: 20 samples without surface damage or deformation were randomly selected from the preforms prepared in each embodiment and comparative example, and then the 20 preform samples were dropped from a height of 2m. Each sample was dropped 100 times, and the number of preforms with interlayer separation was recorded.

[0087] Table 1

[0088] Sample Number of surface damages / piece Deformation quantity / piece Example 1 0 0 Example 2 0 0 Example 3 0 0 Example 4 0 0 Example 5 0 0 Example 6 0 0 Comparative Example 1 14 8 Comparative Example 2 0 0 Comparative Example 3 0 0

[0089] Table 2

[0090]

[0091]

[0092] Table 3

[0093] Sample Number of inter-layer separations Example 1 3 Example 2 1 Example 3 2 Example 4 3 Example 5 2 Example 6 0 Comparative Example 1 - Comparative Example 2 - Comparative Example 3 5

[0094] Table 4

[0095] Sample Light transmittance / % Example 1 91.5 Example 2 90.4 Example 3 92.8 Example 4 91.9 Example 5 92.6 Example 6 92.9 Comparative Example 1 91.3 Comparative Example 2 91.8 Comparative Example 3 93.6

[0096] According to Example 1 and Comparative Example 1 and in combination with the test results in Tables 1-4, it can be seen that when the preform has a single-layer structure and is prepared using the raw material of the inner polyester layer, the dimensional stability of the preform is good, but the demolding property of the preform is poor, and the preform is prone to surface damage or deformation after demolding.

[0097] According to Example 1 and Comparative Example 2 and in combination with the test results in Tables 1-4, it can be seen that when the preform has a single-layer structure and is prepared using the raw material of the outer polyester layer, the demolding property of the preform is good, but the dimensional stability of the preform is reduced, which is not conducive to obtaining a dimensionally stable preform.

[0098] According to Example 1 and Comparative Example 3 and in combination with the test results in Tables 1-4, it can be seen that when PEN resin and PET-PEN copolyester are not added to the inner polyester layer and the outer polyester layer of the preform, the demolding property and transparency of the preform are good, but the dimensional stability of the preform is reduced, which is not conducive to obtaining a dimensionally stable preform.

[0099] According to Example 1 and Example 3-4 and the test results in Table 1-4, it can be known that the PET-PEN copolyester used in the inner polyester layer and the outer polyester layer is preferably a polycondensation product obtained by esterification of terephthalic acid, 2,6-naphthalene dicarboxylic acid and ethylene glycol in a molar ratio of (1.6-1.8): (0.2-0.4): (2.3-2.5), which can improve the compatibility of PET resin and PEN resin and improve the transparency and dimensional stability of the bottle blank.

[0100] According to Example 3 and Example 5-6 and the test results in Table 1-4, it can be seen that the silane coupling agent modified nano-silica in the inner polyester layer adopts aminosilane coupling agent modified nano-silica, and the silane coupling agent modified nano-silica in the outer polyester layer adopts isocyanate silane coupling agent modified nano-silica, which is beneficial to further improve the interlayer bonding stability of the bottle blank.

[0101] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A preform structure that is easy to demould, characterized in that: The invention comprises an inner polyester layer (1) and an outer polyester layer (2) which are arranged in sequence from the inside to the outside, wherein the inner polyester layer (1) and the outer polyester layer (2) both comprise PET resin, PEN resin, PET-PEN copolyester, silane coupling agent modified nano-silica, antioxidant and release agent; in the inner polyester layer (1), the weight ratio of the PET resin, PEN resin, PET-PEN copolyester, silane coupling agent modified nano-silica, antioxidant and release agent is 100: (25-30): (10-15): (3-5): (1-2): (2-3); in the outer polyester layer (2), the weight ratio of the PET resin, PEN resin, PET-PEN copolyester, silane coupling agent modified nano-silica, antioxidant and release agent is 100: (10-15): (8-12): (3-5): (1-2): (4-6).

2. A preform structure for easy demoulding according to claim 1, characterized in that: The melt index of the PET resin is 0.8-1.2 g / 10 min (260° C. / 2.16 kg).

3. A preform structure for easy demoulding according to claim 1, characterized in that: The melt index of the PEN resin is 10-15 g / 10 min (275° C. / 2.16 kg).

4. The preform structure for easy demoulding according to claim 1, characterized in that: The PET-PEN copolyester is a polycondensation product of terephthalic acid, 2,6-naphthalene dicarboxylic acid and ethylene glycol after esterification, wherein the molar ratio of terephthalic acid, 2,6-naphthalene dicarboxylic acid and ethylene glycol is (1.6-1.8): (0.2-0.4): (2.3-2.5).

5. A preform structure for easy demoulding according to claim 4, characterized in that: The preparation method of the PET-PEN copolyester comprises the following steps: After mixing terephthalic acid, 2,6-naphthalene dicarboxylic acid and ethylene glycol, an esterification reaction is carried out at 220-240° C. to obtain an esterification product; A polycondensation catalyst is added to the esterification product, the vacuum degree of the reaction system is controlled to be 0.1-1 mbar, the temperature is controlled to be 260-290° C., and the reaction is carried out for 3-4 hours to obtain PET-PEN copolyester.

6. A preform structure for easy demoulding according to claim 5, characterized in that: The polycondensation catalyst is a titanate catalyst.

7. The preform structure for easy demoulding according to claim 1, characterized in that: The antioxidant is a combination of antioxidant 1010 and antioxidant 168, and the weight ratio of the antioxidant 1010 to the antioxidant 168 is (1-1.5):

1.

8. The preform structure for easy demoulding according to claim 1, characterized in that: The release agent is silicone masterbatch.

9. A preform structure for easy demoulding according to any one of claims 1 to 8, characterized in that: The silane coupling agent modified nano-silica in the inner polyester layer (1) is nano-silica modified with an aminosilane coupling agent, and the silane coupling agent modified nano-silica in the outer polyester layer (2) is nano-silica modified with an isocyanate silane coupling agent.

10. The method for preparing a preform structure that is easy to demould according to any one of claims 1 to 9, characterized in that: The following steps are involved: The raw materials of the inner polyester layer (1) and the outer polyester layer (2) are respectively added into two material barrels of a double-material injection molding machine, and heated and melted at 300-320° C. to obtain a plastic melt of the inner polyester layer and a plastic melt of the outer polyester layer; The inner polyester layer plastic melt and the outer polyester layer plastic melt are processed into a double-layer bottle blank through an injection molding composite process. The double-layer bottle blank comprises an inner polyester layer (1) and an outer polyester layer (2) arranged in sequence from the inside to the outside. After cooling, the bottle blank is demoulded to obtain a bottle blank structure that is easy to demould.

Citation Information

Patent Citations

  • High-performance double-layer polyester bottle

    CN101172525A

  • High-heat-resistance medicinal polyester bottle and production method thereof

    CN107254148A